Application of the failure mode and effects analysis tool in small Scale agroindustrial supply chains - Castillo, Silvana Elizabeth (2020)
Fil: Castillo, Silvana Elizabet. Universidad Nacional de Salta. Facultad de Ingeniería; Argentina.